Water-based modified polyacrylic acid adhesive for silicon-carbon negative electrode material and preparation method of water-based modified polyacrylic acid adhesive

By preparing a water-based modified polyacrylic adhesive of a silicon carbon negative electrode material, the self-complexation of water-soluble polyimide and modified polyacrylate polymer has been used to generate a mesh structure, which solves the problem of poor cycle stability caused by volume changes in silicon-based negative electrode materials in lithium-ion batteries, and achieves higher electrode life and smoothness of charge and discharge capacity.

CN119709057APending Publication Date: 2025-03-28HUBEI MICROCHEM TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411924567.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The volume of the silicon-based negative electrode material changes greatly during the charging and discharging of lithium-ion batteries, resulting in poor battery cycle stability and unstable interface of material powdering and solid electrolyte.

Method used

A preparation method for water-based modified polyacrylic acid adhesive of a silicon carbon negative electrode material is adopted. The self-complexation of water-soluble polyimide and modified polyacrylate polymer is used to generate a mesh structure, and the conductive resin and conductive agent are added to adjust the conductivity and ionic conductivity of the system, and the pH is adjusted through lithium hydroxide solution, and finally the viscosity adjuster is added to improve the processing performance of the electrode material.

Benefits of technology

The adhesive performance of the adhesive to silicon carbon negative electrode material and current collector is improved, which offsets the expansion effect of silicon particles, improves the electrode life and cycle life, and improves the stability of charge and discharge capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709057A_ABST
    Figure CN119709057A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a water-based modified polyacrylic acid adhesive for a silicon-carbon negative electrode material, and belongs to the technical field of adhesives. The preparation method comprises the following steps: (1) uniformly mixing water-soluble polyimide and PAA modified polyacrylate polymer, and carrying out self-complexing on the two polymers to generate a reticular knot structure; (2) adding conductive resin and a conductive agent to improve the conductivity of the system and the ionic conductivity; (3) adjusting the pH value of the system by adopting a proper amount of lithium hydroxide solution; (4) adding a viscosity modifier to improve the processing performance of the electrode material; and (5) uniformly dispersing the materials. Compared with a conventional graphite negative electrode adhesive CMC, the graphite negative electrode adhesive has more carboxyl groups, and the adhesive performance of the adhesive on a silicon-carbon negative electrode material and a current collector is improved. The expansion effect of silicon particle charging and discharging can be counteracted, the electrode life is prolonged, and the cycle life is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesives, and in particular to a method for preparing a water-based modified polyacrylic acid adhesive for a silicon-carbon negative electrode material and the water-based modified polyacrylic acid adhesive for a silicon-carbon negative electrode material prepared by the preparation method. Background Art

[0002] Silicon-based anode materials are one of the most promising anode materials for next-generation lithium-ion batteries because of their high theoretical lithium storage capacity (4200 mA·h / g) and low delithiation potential (<0.5V), as well as their abundant resources and low price. However, the huge volume change (about 300%) of silicon as anode material during the battery (de)lithiation process has severely limited the commercial application of silicon-based anode materials. The huge volume change will lead to the rupture and crushing of silicon particles, the shedding of active materials, and the instability of the solid electrolyte interface (SEI) during the battery (de)lithiation.

[0003] In order to solve the problem of silicon expansion, compared with the material modification with complex preparation process and high cost, the current simple and effective solution is to prepare a special adhesive for silicon-based negative electrode. For silicon-based negative electrodes with large volume changes, in addition to the functions of ordinary lithium ion adhesives, the adhesive also needs to have a specific structure and performance, that is, to bond the active particles to the current collector through a certain intermolecular force, reduce the material pulverization caused by the volume change of silicon during the charge and discharge cycle, and improve the battery cycle stability.

[0004] When used for silicon-based negative electrodes, the carboxyl groups on the carboxymethyl cellulose (CMC) molecular chain can undergo condensation reactions with the hydroxyl groups on the surface oxide layer of silicon particles to form hydrogen bonds and ion-dipole interactions. This strong interaction can produce a self-healing effect during the expansion and contraction process. At the same time, CMC also swells less in electrolyte solvents. However, CMC has high rigidity and low elongation at break. When used alone, the structure of the pole piece will collapse after rolling under high compaction, and a serious powder loss phenomenon will occur. Based on this characteristic, in actual production, it is generally used in combination with styrene-butadiene rubber (SBR) with high elasticity as a binder, which can significantly improve the powder loss phenomenon after high compaction rolling of the pole piece, and the bonding strength is also improved. Some literature points out that when CMC and SBR are used in combination in graphite negative electrodes, the cycle life of the battery can be significantly improved, while when used in silicon-based negative electrodes, the cycle performance has not been significantly improved compared to using CMC alone.

[0005] Polyacrylic acid-based binder Polyacrylic acid (PAA) has a simple structure, is easy to synthesize and is soluble in water. Its mechanical properties are similar to those of CMC, but it contains a higher concentration of carboxyl functional groups. The mechanical properties of PAA do not change significantly before and after swelling in the electrolyte, which means that the presence of the electrolyte will not have a negative impact on the adhesion of PAA. Many studies have shown that under the same conditions, PAA-Si has better cycle performance than CMC-Si. This phenomenon is attributed to the higher concentration of carboxylic acid groups in PAA than in CMC. However, conventional PAA polymers generally have a low molecular weight and a hard straight chain molecular chain, which is not suitable for silicon-based materials with high expansion properties. Summary of the invention

[0006] In view of this, in order to solve the above-mentioned shortcomings of the existing silicon-based negative electrode dedicated adhesive, on the one hand, the present invention provides a method for preparing a water-based modified polyacrylic acid adhesive for silicon-carbon negative electrode materials, which has more carboxyl groups than conventional graphite negative electrode adhesive CMC, and improves the adhesive's bonding performance to silicon-carbon negative electrode materials and current collectors. It can offset the expansion effect of silicon particles during charge and discharge, increase electrode life, and improve cycle life.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] A method for preparing a water-based modified polyacrylic acid adhesive for a silicon-carbon negative electrode material comprises the following steps:

[0009] Step (1), the water-soluble polyimide and the PAA-modified polyacrylate polymer are uniformly mixed, and the two polymers undergo self-complexation to produce a network structure;

[0010] Step (2), adding conductive resin and conductive agent to improve the electrical conductivity and ionic conductivity of the system;

[0011] Step (3), using an appropriate amount of lithium hydroxide solution to adjust the pH of the system;

[0012] Step (4), adding a viscosity modifier to improve the processing performance of the electrode material;

[0013] Step (5), dispersing the above materials evenly.

[0014] Preferably, in step (1), the preparation method of the PAA-modified polyacrylate polymer comprises the following steps:

[0015] Acrylic acid, acrylic acid ester and emulsifier are added into deionized water, stirred evenly under the protection of inert gas, heated to 45-85° C., and free radical initiator is added to react to obtain PAA modified polyacrylate polymer.

[0016] Preferably, the free radical initiator is ammonium persulfate.

[0017] Preferably, the emulsifier is one of polyoxyethylene-400, polyoxyethylene-600 and OP-10.

[0018] Preferably, the acrylate is one of isopropyl acrylate, butyl acrylate, isooctyl acrylate, ethyl methacrylate and butyl methacrylate.

[0019] Preferably, in step (1), the mass percentage of the water-soluble polyimide is 20 to 30 (w / w)%, and the mass percentage of the PAA-modified polyacrylate polymer is 40 to 60 (w / w)%.

[0020] Preferably, in step (2), the mass percentage of the conductive resin is 10 to 20 (w / w) %.

[0021] Preferably, the conductive resin is PEDOT / PSS, and the conductive agent is graphene carbon nanotube conductive paste.

[0022] Preferably, in step (4), the viscosity modifier is carboxymethyl cellulose and hydroxypropyl methyl cellulose.

[0023] On the other hand, the present invention further provides a water-based modified polyacrylic acid adhesive for silicon-carbon negative electrode materials, which is prepared by the preparation method of the water-based modified polyacrylic acid adhesive for silicon-carbon negative electrode materials.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The aqueous PAA modified adhesive prepared by the present invention has more carboxyl groups than the conventional graphite negative electrode adhesive CMC, which improves the adhesive's bonding performance to the silicon-carbon negative electrode material and the current collector.

[0026] (2) In the present invention, since the PAA-modified copolymer has elasticity, it can greatly offset the expansion effect of silicon particles during charging and discharging.

[0027] (3) The cross-linking reaction and complexation between water-soluble polyimine and PAA-modified polymer produce a network structure. The self-healing property of the material makes the electrode less prone to damage, thereby increasing the electrode life and improving the cycle life.

[0028] (4) Lithiated PAA and aqueous improved system ionic conductivity can enhance lithium ion diffusion in electrode materials and improve the stability of charge and discharge capacity.

[0029] (5) Due to the combined effect of the adhesive prepared by the imine additive and the viscosity additive, the gram capacity of the silicon-carbon negative electrode increased from 450 to 850 mAh / g, an increase of 88.9%.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) The aqueous PAA modified adhesive prepared by the present invention has more carboxyl groups than the conventional graphite negative electrode adhesive CMC, which improves the adhesive's bonding performance to the silicon-carbon negative electrode material and the current collector.

[0032] (2) In the present invention, since the PAA-modified copolymer has elasticity, it can greatly offset the expansion effect of silicon particles during charging and discharging.

[0033] (3) The cross-linking reaction and complexation between water-soluble polyimine and PAA-modified polymer produce a network structure. The self-healing property of the material makes the electrode less prone to damage, thereby increasing the electrode life and improving the cycle life.

[0034] (4) Lithiated PAA and aqueous improved system ionic conductivity can enhance lithium ion diffusion in electrode materials and improve the stability of charge and discharge capacity.

[0035] (5) Due to the combined effect of the adhesive prepared by the imine additive and the viscosity additive, the gram capacity of the silicon-carbon negative electrode increased from 450 to 850 mAh / g, an increase of 88.9%. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is the gram capacity curve of Example 1.

[0037] Figure 2 This is the gram capacity curve of Comparative Example 1.

[0038] Figure 3 This is the gram capacity curve of Comparative Example 2.

[0039] Figure 4 This is the gram capacity curve of Comparative Example 3. DETAILED DESCRIPTION

[0040] The present invention provides a method for preparing a water-based modified polyacrylic acid adhesive for a silicon-carbon negative electrode material, comprising the following steps:

[0041] Step (1), water-soluble polyimide and PAA-modified polyacrylate polymer are mixed evenly, and the two polymers undergo self-complexation to produce a network structure. Wherein, the PAA-modified polyacrylate polymer can be a conventional PAA-modified polyacrylate polymer in the art. The present invention provides a preferred method for preparing the PAA-modified polyacrylate polymer, which is as follows:

[0042] Acrylic acid, acrylic acid ester and emulsifier are added into deionized water, stirred evenly under the protection of inert gas, heated to 45-85° C., and free radical initiator is added to react to obtain PAA modified polyacrylate polymer.

[0043] Wherein, the free radical initiator is ammonium persulfate.

[0044] The emulsifier is one of polyoxyethylene-400, polyoxyethylene-600 and OP-10.

[0045] The acrylate is one of isopropyl acrylate, butyl acrylate, isooctyl acrylate, ethyl methacrylate and butyl methacrylate.

[0046] Step (2), adding a conductive resin and a conductive agent to improve the conductivity and ionic conductivity of the system. Among them, the conductive resin is preferably PEDOT / PSS, and the conductive agent is a graphene carbon nanotube conductive slurry. PEDOT / PSS is an aqueous solution of a high molecular polymer with high conductivity. It is composed of two substances, PEDOT and PSS. PEDOT is a polymer of EDOT (3,4-ethylenedioxythiophene monomer), and PSS is polystyrene sulfonate. These two substances together greatly improve the solubility of PEDOT. The aqueous solution conductive material is mainly used in the hole transport layer of organic light emitting diodes OLED, organic solar cells, organic thin film transistors, supercapacitors, etc.

[0047] Step (3), using an appropriate amount of lithium hydroxide solution to adjust the system pH, wherein the pH is preferably 7-8.

[0048] Step (4), adding a viscosity modifier to improve the processing performance of the electrode material. The viscosity modifier is carboxymethyl cellulose and hydroxypropyl methyl cellulose.

[0049] Step (5), dispersing the above materials evenly.

[0050] In the present invention, in step (1), the mass percentage of the water-soluble polyimide is 20 to 30 (w / w)%, and the mass percentage of the PAA-modified polyacrylate polymer is 40 to 60 (w / w)%.

[0051] In the present invention, in step (2), the mass percentage of the conductive resin is 10 to 20 (w / w) %.

[0052] Preparation Example

[0053] Step (1), water-soluble polyimide and PAA-modified polyacrylate polymer are uniformly mixed, and the two polymers undergo self-complexation to produce a network structure; wherein the water-soluble polyimide accounts for 25 (w / w)% of the total raw material mass of the adhesive, and the PAA-modified polyacrylate polymer accounts for 50 (w / w)% of the total raw material mass of the adhesive.

[0054] Step (2), adding conductive resin and conductive agent to improve the conductivity and ionic conductivity of the system, wherein the conductive resin accounts for 15 (w / w)% of the total raw material mass of the adhesive, and the conductive agent accounts for 5 (w / w)% of the total raw material mass of the adhesive.

[0055] Step (3), using an appropriate amount of lithium hydroxide solution to adjust the pH of the system.

[0056] Step (4), adding a viscosity modifier to improve the processing performance of the electrode material. The viscosity modifier accounts for 5 (w / w)% of the total raw material mass of the adhesive.

[0057] Step (5), dispersing the above materials evenly.

[0058] The adhesive prepared in this preparation example was named NJ-06 adhesive.

[0059] The technical solution of the present invention is clearly described in detail below in conjunction with specific embodiments.

[0060] The GT-01 silicon-carbon negative electrode material in the following examples and comparative examples is the silicon-carbon negative electrode material prepared in Example 3 of the invention patent with publication number CN118099362A;

[0061] TJJ-02 additive selection selects one or more of lithium polyimide, lithium bis(fluorosulfonyl)imide, lithium bis(fluorooxalatoborate), and lithium benzoylsulfonylimide.

[0062] Example 1

[0063] GT-01 silicon-carbon negative electrode material (patent announcement number: CN118099362A), NJ-06 adhesive, CCB conductive carbon black and TJJ-02 additive are used; among which, the TJJ-02 additive is polyimide lithium.

[0064] Prepare silicon-carbon negative electrode sheet, ratio (w / w) %: GT: NJ: TJJ: CCB = 75: 10: 10: 5. Test performance as follows Figure 1 As shown in the figure, due to the combined effect of the binder and the additive, the gram capacity of the silicon-carbon negative electrode increased from 450 to 850 mAh / g, an increase of 88.9%, with a smooth charge and discharge curve and high cycle efficiency. Figure 1 shown.

[0065] Comparative Example 1

[0066] The silicon-carbon negative electrode sheet is prepared by using conventional CMC (hydroxymethyl cellulose) adhesive, GT-01 silicon-carbon negative electrode material, TJJ-02 additive and CCB conductive carbon black. Among them, the TJJ-02 additive is polyimide lithium.

[0067] Ratio (w / w) %: GT: CMC: TJJ: CCB = 75: 2: 10: 5. Its test performance is as follows Figure 2 As shown. The capacity starts low, the charge and discharge curve is extremely irregular, and the efficiency of charge and discharge for 1000 cycles does not drop much compared to normal. The rising section of 350-450mAh / g in the first 350 cycles is caused by the large diffusion resistance of the material electrolyte or lithium ions under this condition. The capacity of grams is about 460 in 350-780 cycles, and it is a plateau period. The capacity of grams is 420mAh / g in 700-1000 cycles, and there is no obvious drop in charge and discharge efficiency. Compared with the plateau period, the efficiency drops to 91.1% in the later period, indicating that the silicon-carbon material has excellent cycle performance.

[0068] Comparative Example 2

[0069] Conventional CMC (hydroxymethyl cellulose) adhesive, GT-01 silicon-carbon negative electrode material, TJJ-02 additive and CCB conductive carbon black are used. Among them, TJJ-02 additive is polyimide lithium.

[0070] Ratio (w / w) %: GT: CMC: TJJ: CCB: TJJ = 88: 2: 5: 5 Other conditions are the same as those in Comparative Example 1. Test performance is as follows Figure 3 As shown, the additive increases the gram capacity from 460 to 550-600 mAh / g, and the charge and discharge curves are also much more regular, indicating that the lithium ion conductivity and the diffusion of the electrolyte in the negative electrode are improved.

[0071] Comparative Example 3

[0072] NJ-06 adhesive, GT-01 silicon-carbon negative electrode material and CCB conductive carbon black were used. Other conditions were the same as those in Comparative Example 1. Test performance Figure 4 As shown, it can be seen that the charge and discharge curves are very flat, the charge and discharge are stable, the gram capacity is maintained at about 450mAh / g, and the 120-cycle charge and discharge efficiency is close to 100%, which is significantly better than the performance of CMC adhesive.

Claims

1. A method for preparing a water-based modified polyacrylic acid adhesive for a silicon-carbon negative electrode material, characterized in that: The steps include: Step (1), the water-soluble polyimide and the PAA-modified polyacrylate polymer are uniformly mixed, and the two polymers undergo self-complexation to produce a network structure; Step (2), adding conductive resin and conductive agent to improve the electrical conductivity and ionic conductivity of the system; Step (3), using an appropriate amount of lithium hydroxide solution to adjust the pH of the system; Step (4), adding a viscosity modifier to improve the processing performance of the electrode material; Step (5), dispersing the above materials evenly.

2. The method for preparing a water-based modified polyacrylic acid adhesive for silicon-carbon negative electrode materials according to claim 1, characterized in that: In step (1), the preparation method of PAA modified polyacrylate polymer comprises the following steps: Acrylic acid, acrylic acid ester and emulsifier are added into deionized water, stirred evenly under the protection of inert gas, heated to 45-85° C., and free radical initiator is added to react to obtain PAA modified polyacrylate polymer.

3. The method for preparing a water-based modified polyacrylic acid adhesive for silicon-carbon negative electrode materials according to claim 2, characterized in that: The free radical initiator was ammonium persulfate.

4. The method for preparing a water-based modified polyacrylic acid adhesive for silicon-carbon negative electrode materials according to claim 2, characterized in that: The emulsifier is one of polyoxyethylene-400, polyoxyethylene-600 and OP-10.

5. The method for preparing a water-based modified polyacrylic acid adhesive for silicon-carbon negative electrode materials according to claim 2, characterized in that: The acrylate is one of isopropyl acrylate, butyl acrylate, isooctyl acrylate, ethyl methacrylate and butyl methacrylate.

6. The method for preparing a water-based modified polyacrylic acid adhesive for silicon-carbon negative electrode materials according to claim 1, characterized in that: In step (1), the mass percentage of the water-soluble polyimide is 20 to 30 (w / w)%, and the mass percentage of the PAA-modified polyacrylate polymer is 40 to 60 (w / w)%.

7. The method for preparing a water-based modified polyacrylic acid adhesive for silicon-carbon negative electrode materials according to claim 1, characterized in that: In step (2), the mass percentage of the conductive resin is 10 to 20 (w / w) %.

8. The method for preparing a water-based modified polyacrylic acid adhesive for silicon-carbon negative electrode materials according to claim 7, characterized in that: The conductive resin is PEDOT / PSS, and the conductive agent is graphene carbon nanotube conductive paste.

9. The method for preparing a water-based modified polyacrylic acid adhesive for silicon-carbon negative electrode materials according to claim 1, characterized in that: In step (4), the viscosity modifiers are carboxymethyl cellulose and hydroxypropyl methyl cellulose.

10. A water-based modified polyacrylic acid adhesive for silicon-carbon negative electrode materials, characterized in that: The silicon-carbon negative electrode material is prepared by the preparation method of a water-based modified polyacrylic acid adhesive according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Silicon-carbon negative electrode and preparation method thereof

    CN118099362A